Differences by degree: the access and participation plans of further education colleges and universities. (30th April 2022) - Baldwin, John; Raven, Neil; Webber-Jones, Robin
If an English higher education institution wishes to charge higher tuition fees it must produce an access and participation plan to indicate how it intends to recruit students from under-represented backgrounds. This article evaluates the impact that the regime for producing access and participation plans (APPs) in England has had on further education colleges [FECs] that offer higher education courses. It explores the history of the introduction of APPs and how they are produced. Comparisons are made of paired universities and further education colleges. In particular, consideration is given to the content of the plans and the work imposed on the institutions in producing plans, with questions raised over whether the same APP regime should be imposed on colleges considering the major differences in character and focus between FECs and universities. The article concludes by advocating changes to the process of completing APPs by colleges.